Pengaruh Struktur Kepemilikan, Struktur Aset dan Profitabilitas Terhadap Kebijakan Hutang - Eny Purwaningsih; Zefanya Gabriella Gulo (Jurnal Ilmu Akuntansi, 2021)
Recently the company must have the ability to manage the company's funding sources as well to avoid company losses so the purpose of this study is to find out empirically about the influence of managerial ownership structure, institutional ownership structure, foreign ownership structure, asset structure, and profitability on debt policy in partially or simultaneously in Food and Beverage sub-sector at Manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2020 period. This study uses a type of causal comparative research which is used to determine the relationship between cause and effect on two or more variables. The sample in this study is the Food and Beverage sub-sector at Manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period using the purposive sampling method. There are 6 companies that meet the criteria of the research sample, so the sample is 30 financial statements. The results showed that partially there was a significant and significant influence of institutional ownership (IOWN), foreign ownership (FOWN), and profitability (NPM) variables on debt policy, while managerial ownership (MOWN) and asset structure (FASDR) variables had no influence on debt policy. Simultaneously there is influence of managerial ownership (MOWN), institutional ownership (IOWN), foreign ownership (FOWN), asset structure (FASDR) and profitability (ROE) on debt policy.